Kinetics and mechanism of the alkaline hydrolysis of securinine - Lajis, Nordin H.; Khan, Mohammad Niyaz; M. Noor, Hamdan (1995)
The hydroxide ion‐catalyzed hydrolysis of securinine involves the ring opening of the lactone moiety. The rate of hydrolysis is insensitive to the ionic strength. The observed pseudo‐first‐order rate constants reveal a decrease of approximately 4‐fold due to the increase in the MeCN content from 4 to 50% (v/v) in mixed aqueous solvent. The temperature dependence of the rate of hydrolysis follows the Eyring equation, which yields ΔH* and ΔS* as 11.0 kcal mol−1 and –34.5 cal deg−1 mol−1, respectively. The hydroxy carboxylate product of the alkaline hydrolysis of securinine is shown to undergo cyclization in acidic medium to yield securinine. The observed pseudo‐first‐order rate constants for cyclization increase linearly with an increase in [H+]. The change in the content of MeCN from 3.8 to 47.2% (v/v) in mixed aqueous solvents does not show an effect on the rate of the cyclization reaction. The most plausible mechanisms for alkaline hydrolysis and acid cyclization reactions are also discussed. Copyright © 1995 Wiley‐Liss, Inc., A Wiley Company